Mitigating a COVID-19 outbreak among Major League Baseball players - United States, 2020 - Murray, M. T.; Riggs, M. A.; Engelthaler, D. M.; Johnson, C.; Watkins, S.; Longenberger, A.; Brett-Major, D. M.; Lowe, J.; Broadhurst, M. J.; Ladva, C. N.; Villanueva, J. M.; MacNeil, A.; et al. (MMWR Morbidity Mortal Weekly Report, 2020)
Mass gatherings have been implicated in higher rates of transmission of SARS-CoV-2, the virus that causes coronavirus disease 2019 (COVID-19), and many sporting events have been restricted or canceled to limit disease spread (1). Based on current CDC COVID-19 mitigation recommendations related to events and gatherings (2), Major League Baseball (MLB) developed new health and safety protocols before the July 24 start of the 2020 season. In addition, MLB made the decision that games would be played without spectators. Before a three-game series between teams A and B, the Philadelphia Department of Public Health was notified of a team A player with laboratory-confirmed COVID-19; the player was isolated as recommended (2). During the series and the week after, laboratory-confirmed COVID-19 was diagnosed among 19 additional team A players and staff members and one team B staff member. Throughout their potentially infectious periods, some asymptomatic team A players and coaches, who subsequently received positive SARS-CoV-2 test results, engaged in on-field play with teams B and C. No on-field team B or team C players or staff members subsequently received a clinical diagnosis of COVID-19. Certain MLB health and safety protocols, which include frequent diagnostic testing for rapid case identification, isolation of persons with positive test results, quarantine for close contacts, mask wearing, and social distancing, might have limited COVID-19 transmission between teams.